2018
DOI: 10.1093/jpids/piy030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Nephrotoxicity Among Pediatric Patients Receiving Vancomycin With Either Piperacillin–Tazobactam or Cefepime: A Cohort Study

Abstract: Among hospitalized children at our institution, combination therapy with vancomycin and TZP was associated with an incidence of AKI higher than that associated with vancomycin and cefepime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
1
35
1
4
Order By: Relevance
“…In this cohort of pediatric heme/onc patients, exposure to vancomycin plus pip/tazo was associated with higher rates of AKI than exposure to vancomycin plus cefepime. The AKI rates we observed in the study groups were similar to those found in a large multicenter pediatric study (11.7% for pip/tazo vs 4.0% for other beta‐lactams), but lower than previously found at our institution (28.9% for pip/tazo vs 7.9% for cefepime) in a study among hospitalized children, many who had undergone cardiac surgery . Our AKI rates were also lower than those found in studies of adults .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this cohort of pediatric heme/onc patients, exposure to vancomycin plus pip/tazo was associated with higher rates of AKI than exposure to vancomycin plus cefepime. The AKI rates we observed in the study groups were similar to those found in a large multicenter pediatric study (11.7% for pip/tazo vs 4.0% for other beta‐lactams), but lower than previously found at our institution (28.9% for pip/tazo vs 7.9% for cefepime) in a study among hospitalized children, many who had undergone cardiac surgery . Our AKI rates were also lower than those found in studies of adults .…”
Section: Discussionsupporting
confidence: 84%
“…for cefepime) in a study among hospitalized children, many who had undergone cardiac surgery. 3,4 Our AKI rates were also lower than those found in studies of adults. 2,8 Regardless of these differences, taken together, these studies suggest that the combination of vancomycin plus pip/tazo is more nephrotoxic than vancomycin plus other beta-lactam antibiotics.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Previous studies investigated the nephrotoxicity of those two combinations by choosing one drug (cefepime) from the cephalosporin class as an example for the entire group [17,20], but our results were inconsistent with theirs. Cook et al evaluated the incidence of AKI development in VAN-PTZ vs VAN + cefepime in the pediatric population (VAN-PTZ 28.9% vs VAN + cefepime 7.9%, p-value = 0.001) [19]. Another unmatched study by Gomes et al in 2014 showed that the VAN-PTZ combination caused AKI more frequently than the VAN + cefepime combination in adults (VAN-PTZ 34.8% vs VAN + cefepime 12.5%, p-value = 0.0001) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher rates of nephrotoxicity were observed among patients treated with VAN-PTZ compared with VAN treatment alone; however, the exact mechanism for the increased nephrotoxicity by this combination was not fully understood [18]. Moreover, a robust retrospective cohort study reported a higher incidence of AKI in pediatric patients using VAN-PTZ compared to VAN-cefepime [19].…”
Section: Introductionmentioning
confidence: 99%